Acoustic visualization of scleral outflow after surgical scleral resection - A.Yu. Kazantzeva; E.A. Korchuganova (РМЖ "Клиническая офтальмология")
A.Yu. Kazantseva, E.A. Korchuganova Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to assess the functionality of new surgical outflow pathways by ultrasound biomicroscopy (UBM) in primary open-angle glaucoma (POAG) and neovascular glaucoma (NVG) after surgical scleral resection (SSR). Patients and Methods: a total of 67 patients (67 eyes) with advanced and end-stage POAG and 17 patients (17 eyes) with advanced and end-stage NVG who underwent SSR were examined. Eye examinations included biomicroophthalmoscopy, visual acuity measurement, IOP measurement using a Maklakov applanation tonometer, automated perimetry, tonography, and UBM. UBM was employed to evaluate the acoustic signs of new surgical filtering areas, namely the intrascleral space and filtering bleb (FB) height. UBM was performed in the early (4 weeks) and late (24 and 36 months) postoperative periods following SSR. Results: 4 weeks after SSR, a diffuse, somewhat loose FB was observed in all patients. The mean FB height was 0.49±0.06 mm in patients with POAG and 0.42±0.03 mm in patients with NVG. The mean IOP was 19.0±0.25 mm Hg and 21.2±1.05 mm Hg, respectively. Twenty-four months after SSR, FB height was 0.55±0.02 mm in patients with POAG and 0.46±0.04 mm in patients with NVG. Mean IOP was 18.00±0.31 mm Hg and 20.1±0.65 mm Hg, respectively. By the conclusion of the follow-up period (36 months), the FB exhibited a tendency towards flattening in the majority of patients, with an average height of 0.40±0.06 mm in patients with POAG and 0.34±0.02 mm in patients with NVG (controlled IOP). Conclusion: UBM provided reliable evidence of FB formation, which persisted for more than three years following non-penetrating SSR in the context of controlled IOP in POAG and NVG. Keywords: surgical scleral resection, uveoscleral outflow, ultrasound biomicroscopy, hypoechoic intrascleral space, filtering bleb, IOP. For citation: Kazantseva A.Yu., Korchuganova E.A. Acoustic visualization of scleral outflow after surgical scleral resection. Russian Journal of Clinical Ophthalmology. 2024;24(2):60–63 (in Russ.). DOI: 10.32364/2311-7729-2024-24-2-3.